A patient with acute pulmonary embolism caused by hyaluronic acid injection underwent nursing care of extracorporeal membrane oxygenation support therapy: a case report - Wang, Yan; Deng, Qidan; Tang, Shili; Yu, Fenhao; Lv, Yunhao; Liu, Zhi; Lin, Lizhen; Lu, Huihui (Frontiers in Medicine, 2025)
This article summarizes the nursing management of a patient who developed acute pulmonary embolism with concomitant cardiopulmonary arrest following intravaginal hyaluronic acid injection, requiring extracorporeal membrane oxygenation (ECMO) support. The main measures are rapid activation of the treatment plan to improve the efficiency of treatment; teamwork and safe transfer; early implementation of target temperature management to promote neurological prognosis; implementation of individualized anticoagulation strategies and infection control strategies; and autologous blood transfusion techniques to reduce blood loss during ECMO withdrawal. After 9 days of active treatment and refined care, the patient’s condition was stable, and she was transferred to the general ward to continue treatment for 2 days and was discharged after recovery. At 1-month follow-up after discharge, the patient’s consciousness was clear, her speech was clear, and the muscle strength of the limbs was back to normal. The cooperation of a mature ECMO team was important in the rescue and treatment of this patient, which could shorten the response time in all aspects of the rescue and improve the success rate of rescue and treatment. The application of individualized therapeutic measures and high-quality nursing care is the key to promote the recovery of this patient.